The Performance of Private Madrasah Aliyah Principals in Enhancing Teacher Quality - Rizka Nur; Candra Wijaya; Neliwati Neliwati (EDUTEC : Journal of Education And Technology, 2023)
This qualitative study explores the role of principals as leaders in improving teacher quality in the Panai Hulu sub-district, Labuhan Batu district. Data was collected through observations, interviews, and documentation methods. Analysis of the data followed Huberman and Miles' approach, including data reduction, data presentation, and drawing conclusions. Additionally, the data's validity was assessed using credibility, transferability, dependability, and confirmability criteria proposed by Lincold and Guba. The findings of this study revealed several strategies implemented by Aliyah Madrasah heads to improve teacher quality, such as collaborating with external parties, providing motivation through training and workshops, maximizing subject teacher deliberations, facilitating continuing education, maintaining teacher resource materials, and conducting teacher supervision activities. The performance of the madrasa heads in enhancing teacher quality was assessed based on competencies such as personality, managerial skills, entrepreneurship, supervision, and social skills. However, various obstacles and constraints were identified, including financial difficulties faced by private madrasahs, resulting in limited resources and heavy reliance on the BOS funds. Additionally, teachers' punctuality and the age-related challenges in utilizing appropriate teaching media were identified as hindrances to improving teacher quality.